(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
In this paper we are interested in investigating how the I of the referential text Volverse Palestina, by the Chilean writer Lina Meruane, is constructed, problematizing the relationship between migration and the themes of memory and identity. Our reading proposal asks about the meaning acquired by the genres chosen by the author to carry out memory and testimonial exercises. The analysis shows the displacement of discursive purposes of the family tree format and of the travel chronic genre, the political-discursive appropriation of the Jewish mandate to remember and the emergence of imagined migrant cartographies.